The Effect of Compensation on the Performance of KSPPS Hudatama Semarang Employees - Dyah Purwaningrum; Sutaat Sutaat (ProBisnis : Jurnal Manajemen, 2023)
KSPPS Hudatama Semarang is an independent business organization that has activities to develop various productive business activities to improve the quality of economic activities carried out by small communities and entrepreneurs. Providing appropriate compensation is one way that can be used to improve performance for employees to achieve the desired performance of the company. At work, Compensation is very important for employees because the size of the compensation is a measure of employee performance. Employees always expect a more adequate income. Based on this view, researchers are interested in conducting research related to compensation for employee performance through the title ". Effect of Compensation on KSPPS Huda Tama Semarang employee performance.” This study aims to determine the effect of compensation on employee performance at KSPPS Hudatama Semarang. The strategy for improving employee performance is expected to be a trigger for work enthusiasm towards the company's vision and mission and can fulfill the rights and obligations of employees at KSPPS Hudatama Semarang. The research method used is quantitative research using a simple linear regression method. The sample in this study amounted to 43 respondents using the census method. Data collection used a questionnaire and data processing used the SPSS Statistics Version 22.0 for Windows.